Correction: Class 1 integron-borne cassettes harboring blaCARB-2 gene in multidrug-resistant and virulent Salmonella Typhimurium ST19 strains recovered from clinical human stool samples, United States. - Daniel F M Monte; Fábio P Sellera; Ralf Lopes; Shivaramu Keelara; Mariza Landgraf; Shermalyn Greene; Paula J Fedorka-Cray; Siddhartha Thakur (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0240978.].